Impact of terminal tip location of midline catheters on catheter‐related complications and indwelling duration in elderly patients. Issue 4 (17th November 2022) - Fu, Jing; Zhao, Lingling; Tian, Yingmei; Liu, Yinmeng; Zhang, Hongyu; Li, Haijun
Abstract: Aim: To investigate the relationship between the position of the midline catheter tip and the frequency and type of complications associated with its placement. Design: A cohort study was performed on patients between May 2018 and December 2021 who underwent midline catheter placement at our institution. Patients were divided into two groups, superficial implementation and deep implementation, based on the midline catheter tip location relative to the clavicle. Methods: Clinical data and outcome parameters, including the numbers and types of midline catheter‐related complications, day of occurrence and catheter indwell duration, were recorded. Results: Catheter‐related complications occurred in 14 individuals. Compared with the superficial implementation group, the incidence of complications in the deep catheterization group was significantly reduced, with a delayed first occurrence time, and a prolonged catheter indwelling time. The results suggested that locating the midline catheter tip in the distal segment of the axillary vein may reduce catheter‐related complication incidence and prolong the indwelling duration.